Algorithm of constructing hybrid effective modules for elastic isotropic composites; IOP Conference Series: Materials Science and Engineering; Vol. 177 : Mechanical Engineering, Automation and Control Systems (MEACS 2016) - Svetashkov A. A. Aleksandr Andreevich; Micinski J.; Kupriyanov N. A. Nikolay Amvrosievich; Barashkov V. N.; Lushnikov A. V. (Numerical simulation of applied problems, 2017)
Title screen